The Simeon chamber - Martini, Steve (New York : Jove Books, 1994)
As Jennifer Davies and her attorney, Sam Bogardus, attempt to search out her natural father with only an ancient parchment for a clue, they discover a deadly web of art theft, intrigue, and murder.
National College of Business and Arts
Keywords: Drake, Francis, -- approximately 1540-1596 -- Fiction; Action and adventure fiction